A bio-based degradable multi-block copolyester elastomer and preparation method thereof
By using low-temperature three-step transesterification-polycondensation process of 2,5-furandiformate and dimethyl dimerate, a multi-block copolyester elastomer with high bio-based carbon content and high molecular weight was prepared to solve the problem of The existing polyester elastomers have low bio-based carbon content and non-degradable problems, and the adjustability of strength and elongation and efficient biodegradability are achieved.
Patent Information
- Application Number
- CN202210362888.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-07
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-04-07
AI Technical Summary
The existing polyester elastomers have low bio-based carbon content, rely on fossil energy, and the decrease in molecular weight affects strength and recovery rate, and are not biodegradable.
Using dimethyl 2,5-furandicarboxylate and dimethyl dimerate as raw materials, a high bio-based carbon content and high molecular weight multi-block copolyester elastomer is prepared through a low-temperature three-step ester exchange-polycondensation process to regulate The ratio of hard and soft segments is to achieve adjustability of strength and elongation.
It improves the bio-based carbon content, molecular weight and mechanical strength of polyester elastomers, maintains an elastic recovery rate of more than 80%. It has the advantages of low energy consumption, few side reactions, light color of products and adjustable performance, and is suitable for industrial applications.
Smart Images

Figure CN114752044B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermoplastic polyester elastomers, and specifically relates to a bio-based degradable multi-block copolyester elastomer based on dimethyl 2,5-furandicarboxylate and dimethyl dimerate and a preparation method thereof. Background Art
[0002] Due to the high elasticity of rubber materials, they have been widely used in industrial production, national defense, daily life, etc., and are considered to be important strategic resources. However, the main raw materials of synthetic rubber, such as styrene, isoprene, butadiene, etc., all come from non-renewable petrochemical resources. As a major consumer of petrochemical resources, the rubber industry produces a large amount of wastewater and waste gas. In order to solve this prominent problem, an effective method is to prepare new bio-based elastomer materials with engineering application potential based on bio-based chemicals.
[0003] Furandicarboxylic acid polyester is a widely studied bio-based polyester, and further research to expand its application range is underway. Dimethyl dimer acid ester (FADA) is completely bio-based, amorphous, and highly flexible, making it suitable as a copolymer soft segment.
[0004] Thermoplastic copolyester elastomers (TPEE) combine high strength, rubber-like elasticity and easy processing. This range of properties can be achieved if the polymer microstructure exhibits microphase separation. Considering the chemical structure, TPEE is a multi-block copolymer composed of polymers with alternating rigid and flexible segments. The rigid segment is formed by polyester, which has the ability to crystallize and a high melting point. The flexible segment is formed by oligomers with a relatively low glass transition temperature and high chain conformation flexibility. The interaction between the rigid segments leads to the formation of crystalline regions of the hard phase, which serve as thermally reversible physical network crosslinking points, providing the strength and dimensional stability of the copolymer. In turn, the amorphous soft phase of the flexible segment provides the flexibility of the material. This special microstructure is thermally reversible, provides excellent processability, and the final properties of the copolymer depend on the content of each block.
[0005] At present, the research on polyester elastomers mainly has these problems: 1) low bio-based carbon content, and the raw materials are strongly dependent on fossil energy; 2) the molecular weight of thermoplastic polyester elastomers containing dimer acid decreases significantly with the increase of dimer acid, affecting the final strength and recovery rate; 3) it is not biodegradable. Therefore, the research and preparation of high bio-based carbon content, high molecular weight and biodegradable polyester elastomers has certain scientific and application significance. Summary of the invention
[0006] Technical problem to be solved: In view of the above defects, the present invention provides a bio-based degradable multi-block copolyester elastomer based on dimethyl 2,5-furandicarboxylate and dimethyl dimer acid ester and a preparation method thereof. By pre-esterifying dimer acid to obtain dimethyl dimer acid ester and copolymerizing the hard segment of 2,5-furandicarboxylic acid polyester with the soft segment of dimer acid polyester under relatively low temperature conditions, a thermoplastic polyester elastomer with high bio-based carbon content, high molecular weight, high mechanical strength and recovery performance can be obtained, which has broad application prospects.
[0007] Technical solution: A bio-based degradable multi-block copolyester elastomer, the structure of which is shown below: R1 is R2 is CH2CH2, CH2CH2CH2, CH2CH(CH3)CH2CH2(CH2)4CH2, CH2CH2CH2CH2, CH2CH2OCH2CH2, CH2C(CH3)2CH2 or m and n are the polymerization degrees of the respective blocks, m is an integer of 0 to 110, and n is an integer of not less than 40.
[0008] When used as a polyester elastomer, the multi-block copolymer wherein R2 is CH2CH2CH2CH2 or
[0009] The preparation method of the above-mentioned bio-based degradable multi-block copolyester elastomer comprises the following steps: (1) in the presence of catalyst A, adding 2,5-furandicarboxylic acid dimethyl ester and dimer acid dimethyl ester in a molar ratio of (2-9):1 into a reactor, adding a small molecule diol, stirring and heating to 160-180°C for ester exchange reaction for 1-6 hours to obtain furandicarboxylic acid dihydroxyalkyl ester and dimer acid dihydroxyalkyl ester, wherein the small molecule diol is a diol corresponding to R2, and the molar ratio of the diol to the dimethyl ester is (1.2-3.0):1.0, and the catalyst A is tetrabutyl titanate, tetraisopropyl titanate, zinc acetate, dibutyltin oxide, stannous octoate, stannous oxalate or lanthanum acetylacetonate, and the catalyst A accounts for 0.2‰ to 1.0% of the total mass of the reactants. 0.8‰; (2) subjecting the mixture of furandicarboxylic acid dihydroxyalkyl ester and dimericarboxylic acid dihydroxyalkyl ester obtained in step (1) to a second ester exchange reaction with an equimolar amount of 2,5-furandicarboxylic acid dimethyl ester to obtain a low molecular weight polyester prepolymer, wherein the molar ratio of the dihydroxyalkyl ester to the 2,5-furandicarboxylic acid dimethyl ester is (2.0-1.0):1.0, and the reaction temperature is 150-220°C; (3) subjecting the low molecular weight polyester prepolymer obtained in step (2) to polycondensation under the action of catalyst B to obtain a bio-based degradable multi-block copolyester elastomer, wherein the polycondensation temperature is 200-220°C, the catalyst B is antimony trioxide, lithium acetylacetonate, zinc acetate or germanium oxide, and the amount of catalyst B used accounts for 0.2‰-0.8‰ of the total mass of the reactants.
[0010] Preferably, the above step (1) is: in the presence of catalyst A and an auxiliary agent, 2,5-furandicarboxylic acid dimethyl ester, dimer acid dimethyl ester and a small molecule diol are mixed and stirred and heated to 160-180°C to carry out an ester exchange reaction. When the collected distillate reaches not less than 95% of the theoretical value, the first step of the reaction is completed to obtain a mixture of furandicarboxylic acid dihydroxyalkyl ester and dimer acid dihydroxyalkyl ester, wherein the molar ratio of the dimethyl ester to the small molecule diol is (1.2-3.0):1. 0; the catalyst A accounts for 0.3‰ to 0.5‰ of the total mass of the reactants; the amount of the auxiliary agent is 0.01 to 1% of the total mass of the monomers, the auxiliary agent is at least one of a heat stabilizer, a light stabilizer or an inorganic filler, the heat stabilizer is dibutyltin oxide or trimethyl phosphate, the light stabilizer is light stabilizer 944, light stabilizer 622, light stabilizer 770, light stabilizer 292 or light stabilizer 783, and the inorganic filler is calcium carbonate, magnesium carbonate or silicon dioxide.
[0011] Preferably, the above step (2) is: to the mixture of dihydroxyalkyl furandicarboxylate and dihydroxyalkyl dimer acid obtained in step (1), an equimolar amount of dimethyl 2,5-furandicarboxylate is continuously added, and the reaction temperature is 150 to 220° C., and the reaction time is 1 to 5 hours to obtain an oligomer, and the reaction is terminated, and the reaction temperature is maintained to carry out step (3).
[0012] Preferably, the above step (3) is: adding catalyst B to the oligomer obtained in step (2), controlling the pressure at 40±5Pa within half an hour, and conducting a vacuum polycondensation reaction at a reaction temperature of 220°C for 2 to 8 hours; the amount of catalyst B used accounts for 0.3‰ to 0.5‰ of the total mass of the reactants.
[0013] Beneficial effects: The present invention uses biomass resources furandicarboxylic acid dimethyl ester and dimer acid dimethyl ester as raw materials, introduces short-chain bio-based or petroleum-based diols, and adopts an improved low-temperature three-step ester exchange-polycondensation process to obtain a bio-based degradable multi-block copolyester elastomer based on 2,5-furandicarboxylic acid dimethyl ester and dimer acid dimethyl ester. The molecular weight of the elastomer is higher than that of the existing report (30000-40000 g / mol), and the corresponding strength and elongation are also improved; by adjusting the ratio of the furandicarboxylic acid polyester hard segment to the dimer acid polyester soft segment, the strength and elongation of the polyester elastomer can be adjusted, and the elastic recovery rate can be maintained at more than 80%, and the elastomer has excellent performance. The preparation method of the present invention has the advantages of low energy consumption, few side reactions, light product color, adjustable performance, etc., which is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is the chemical degradation process of polyester elastomers.
[0015] Figure 2 This is an infrared spectrum of the bio-based degradable multi-block copolyester elastomer based on dimethyl 2,5-furandicarboxylate and dimethyl dimer acid prepared in the present invention.
[0016] Figure 3 The differential scanning calorimetry diagram of the bio-based degradable multi-block copolyester elastomer based on dimethyl 2,5-furandicarboxylate and dimethyl dimer acid prepared by the present invention, wherein (a) the differential scanning calorimetry cooling curve of the polyester elastomer with different proportions; (b) the differential scanning calorimetry heating curve of the polyester elastomer with different proportions.
[0017] Figure 4 The stress-strain curve of the bio-based degradable multi-block copolyester elastomer based on dimethyl 2,5-furandicarboxylate and dimethyl dimer acid prepared in the present invention.
[0018] Figure 5 The cyclic stretching and recovery curves of the bio-based degradable multi-block copolyester elastomer based on dimethyl 2,5-furandicarboxylate and dimethyl dimer acid prepared in the present invention, including (a) the cyclic stretching curve of the PBDF-20 sample; (b) the elastic recovery rate curve of the PBDF-20 sample during the cyclic stretching process. DETAILED DESCRIPTION
[0019] The present invention is further described below in conjunction with specific embodiments.
[0020] The technical scheme of the present invention is further described below in conjunction with examples, but the purpose of these examples is not to limit the scope of protection of the present invention. In these examples, unless otherwise specified, all percentages are by weight.
[0021] In order to obtain the above block copolyester conveniently, simply and efficiently, the reaction equation is:
[0022]
[0023] In order to improve the tensile recovery performance and bio-based carbon content of the elastomer, the small molecule diol is preferably bio-based ethylene glycol, bio-based 1,3-propylene glycol, bio-based 1,4-butanediol, and bio-based isosorbide. This is because the glass transition temperature of the hard segment of the furandicarboxylic acid polyester prepared from short-chain aliphatic / alicyclic diols is high, which plays a good physical cross-linking role in the elastomer. As the molecular weight of the small molecule linear diol increases, the glass transition temperature of the corresponding hard segment will decrease significantly, which is not conducive to the improvement of the tensile properties of the multi-block copolyester elastomer material;
[0024] In order to increase the molecular weight of the elastomer, dimer acid is pre-esterified to obtain dimer acid dimethyl ester, which is then involved in a polycondensation reaction to prepare a multi-block copolyester elastomer. Currently, the molecular weight of the thermoplastic polyester elastomer containing dimer acid, which is widely studied, decreases significantly with the increase of dimer acid, affecting the final strength and recovery rate; the present invention replaces dimer acid with dimer acid dimethyl ester, and replaces the high activation energy esterification reaction with a low activation energy ester exchange reaction, which greatly increases the molecular weight of the polyester.
[0025] In order to lower the polycondensation temperature and reduce discoloration, the above step (2) is: the dihydroxyalkyl ester obtained in step (1) is subjected to a second ester exchange reaction with an appropriate amount of 2,5-furandicarboxylic acid dimethyl ester to obtain a polyester prepolymer, and the molar ratio of the dihydroxyalkyl ester / 2,5-furandicarboxylic acid dimethyl ester is (2.0-1.0):1.0. Preferably, the molar ratio of the furandicarboxylic acid dihydroxyalkyl ester to 2,5-furandicarboxylic acid dimethyl ester is (1.2-1.0):1.0. This is because at this ratio, the molar ratio of the hydroxyl group and the methyl ester group in the system is close to 1:1, and the relatively highly active de-methanolation ester exchange reaction mainly occurs during the polycondensation process. Compared with the traditional de-esterification reaction of small molecular diols such as ethylene glycol, propylene glycol, and butanediol, this process reaction has a lower activation energy, and a high molecular weight polyester can be obtained at a relatively lower temperature.
[0026] In order to achieve the degradable properties of the elastomer, the chemical degradation method is preferred. The elastomer polyester strip that has been broken by pulling is placed in an appropriate amount of methanol, and chemically degraded at 150°C for 24 hours without adding any catalyst or additive, and finally a transparent liquid is obtained. It includes dimethyl dimer, dimethyl 2,5-furandicarboxylate, small molecule diols and degradation agent methanol. After removing methanol, the remaining raw materials can be polymerized again to prepare bio-based elastomer materials. The specific process is as follows Figure 1 shown.
[0027] Embodiment 1:
[0028] Preparation of biodegradable multi-block copolyester elastomer based on dimethyl 2,5-furandicarboxylate and dimethyl dimerate:
[0029] Using 98% concentrated sulfuric acid as a catalyst, high-purity dimer acid (dimer content> 98%) and methanol were refluxed for 2 hours at a molar ratio of 1:8 to obtain dimer acid dimethyl ester.
[0030] In a flask equipped with a constant temperature overhead stirrer, a distillation tower, a temperature measuring device and a nitrogen gas supply device, 0.23 mol (42.32 g) of dimethyl 2,5-furandicarboxylate, 0.59 mol (53.10 g) of ethylene glycol, 0.067 mol (39.40 g) of dimethyl dimerate and 0.08 g of tetraisopropyl titanate were added, and the mixture was reacted at 160°C for 2 hours, 170°C for 2 hours and 180°C for 2 hours under a nitrogen atmosphere to obtain an ester exchange product.
[0031] The temperature was lowered to 140-150° C., 0.29 mol (53.36 g) of dimethyl 2,5-furandicarboxylate was added, the temperature was raised to 160° C., and the temperature was raised to 200° C. at a heating rate of 10° C. / h under a nitrogen atmosphere to obtain an oligomer.
[0032] Add 0.08 g of zinc acetate, stir and gradually heat to 200°C, reduce the system pressure to 40±5 Pa within 30 minutes, then increase the temperature to 220°C and perform vacuum polycondensation for 6 hours. When the torque of the stirring shaft no longer increases, stop the reaction.
[0033] The final product PBDF-20 is a thermoplastic elastomer. Combined with the tensile data in the figure, its molecular weight is greater than 50,000 g / mol, the tensile strength is about 24 MPa, the elongation at break is close to 550%, and after 10 cyclic tensile tests, the elastic recovery rate remains above 80%, which is a bio-based polyester elastomer material with excellent performance.
[0034] Embodiment 2:
[0035] Bio-based degradable multi-block copolyester elastomer based on dimethyl 2,5-furandicarboxylate and dimethyl dimerate:
[0036] Using concentrated sulfuric acid as a catalyst, high-purity dimer acid (dimer content> 98%) and methanol were refluxed for 2 hours at a molar ratio of 1:8 to obtain dimer acid dimethyl ester.
[0037] In a flask equipped with a constant temperature overhead stirrer, a distillation tower, a temperature measuring device and a nitrogen gas supply device, 0.22 mol (40.48 g) of dimethyl 2,5-furandicarboxylate, 0.68 mol (42.16 g) of 1,4-butanediol, 0.09 mol (52.92 g) of dimethyl dimerate and 0.12 g of tetrabutyl titanate were added, and the mixture was reacted at 160°C for 2 hours, 170°C for 2 hours and 180°C for 2 hours under a nitrogen atmosphere to obtain an ester exchange product.
[0038] The temperature was lowered to 140-150° C., 0.25 mol (46.00) of dimethyl 2,5-furandicarboxylate was added, the temperature was raised to 160° C., and the temperature was raised to 200° C. at a heating rate of 10° C. / h under a nitrogen atmosphere to obtain an oligomer.
[0039] Add 0.06 g of germanium oxide, stir and gradually heat to 200°C, reduce the system pressure to 40±5 Pa within 30 minutes, then increase the temperature to 220°C and perform vacuum polycondensation for 5 hours. When the torque of the stirring shaft no longer increases, stop the reaction.
[0040] The final product PBDF-30 is a thermoplastic elastomer. Combined with the tensile data in the figure, its molecular weight is greater than 50,000 g / mol, its tensile strength is about 10 MPa, and its elongation at break is greater than 500%. After 10 cyclic tensile tests, the elastic recovery rate remains above 80%, making it a bio-based polyester elastomer material with excellent performance.
[0041] Embodiment 3:
[0042] Bio-based degradable multi-block copolyester elastomer based on dimethyl 2,5-furandicarboxylate and dimethyl dimerate:
[0043] Using concentrated sulfuric acid as a catalyst, high-purity dimer acid (dimer content> 98%) and methanol were refluxed for 2 hours at a molar ratio of 1:8 to obtain dimer acid dimethyl ester.
[0044] In a flask equipped with a constant temperature overhead stirrer, a distillation tower, a temperature measuring device and a nitrogen gas supply device, 0.33 mol (60.72 g) of dimethyl 2,5-furandicarboxylate, 0.44 mol (63.36 g) of 1,4-cyclohexanedimethanol, 0.035 mol (20.58 g) of dimethyl dimerate and 0.10 g of lanthanum acetylacetonate were added, and the mixture was reacted at 160°C for 2 hours, 170°C for 2 hours and 180°C for 2 hours under a nitrogen atmosphere to obtain an ester exchange product.
[0045] The temperature was lowered to 140-150° C., 0.29 mol (53.36 g) of dimethyl 2,5-furandicarboxylate was added, the temperature was raised to 160° C., and the temperature was raised to 200° C. at a heating rate of 10° C. / h under a nitrogen atmosphere to obtain an oligomer.
[0046] Add 0.1 g of antimony trioxide, stir and gradually heat to 200°C, reduce the system pressure to 40±5 Pa within 30 minutes, then increase the temperature to 220°C and perform vacuum polycondensation for 5 hours. When the torque of the stirring shaft no longer increases, stop the reaction.
[0047] The final product PBDF-10 is a thermoplastic elastomer. Combined with the tensile data in the figure, its molecular weight is greater than 80,000 g / mol, its tensile strength is about 27 MPa, and its elongation at break is greater than 400%. After 10 cyclic tensile tests, the elastic recovery rate remains above 80%, making it a bio-based polyester elastomer material with excellent performance.
[0048] Table 1 Composition and molecular weight distribution of bio-based degradable multi-block copolyester elastomer based on dimethyl 2,5-furandicarboxylate and dimethyl dimer acid prepared by the present invention
[0049]
Claims
1. A method for preparing a bio-based degradable multi-block copolyester elastomer, characterized in that: The method comprises the following steps: (1) in the presence of a catalyst A, adding dimethyl 2,5-furandicarboxylate and dimethyl dimerate in a molar ratio of (2-9):1 into a reactor, adding a small molecule diol, stirring and heating to 160-180°C for ester exchange reaction for 1-6 hours to obtain dihydroxyalkyl furandicarboxylate and dihydroxyalkyl dimerate, wherein the molar ratio of the diol to the dimethyl ester is (1.2-3.0):1.0, and the catalyst A is tetrabutyl titanate, tetraisopropyl titanate, zinc acetate, dibutyltin oxide, stannous octoate, stannous oxalate or lanthanum acetylacetonate, and the catalyst A accounts for 1% of the total mass of the reactants. The reaction temperature is 150-220°C; (3) the low molecular weight polyester prepolymer obtained in step (2) is subjected to polycondensation under the action of catalyst B to obtain a bio-based degradable multi-block copolyester elastomer, the polycondensation temperature is 200-220°C, the catalyst B is antimony trioxide, lithium acetylacetonate, zinc acetate or germanium oxide, and the amount of catalyst B is 0.2‰-0.8‰ to the total mass of the reactants.
2. The preparation method according to claim 1, characterized in that: The step (1) comprises: in the presence of catalyst A and an auxiliary agent, mixing 2,5-furandicarboxylic acid dimethyl ester, dimer acid dimethyl ester and a small molecule diol, stirring and heating to 160-180° C., and performing an ester exchange reaction; when the collected distillate reaches not less than 95% of the theoretical value, the first step of the reaction is completed to obtain a mixture of furandicarboxylic acid dihydroxyalkyl ester and dimer acid dihydroxyalkyl ester, wherein the molar ratio of the dimethyl ester to the small molecule diol is 1.0:(1.2-3.0); The catalyst A accounts for 0.3‰ to 0.5‰ of the total mass of the reactants; the amount of the auxiliary agent is 0.01 to 1% of the total mass of the monomers, and the auxiliary agent is at least one of a heat stabilizer, a light stabilizer or an inorganic filler. The heat stabilizer is dibutyltin oxide or trimethyl phosphate, the light stabilizer is light stabilizer 944, light stabilizer 622, light stabilizer 770, light stabilizer 292 or light stabilizer 783, and the inorganic filler is calcium carbonate, magnesium carbonate or silicon dioxide.
3. The preparation method according to claim 1, characterized in that: The step (2) comprises: adding an equal molar amount of dimethyl 2,5-furandicarboxylate to the mixture of dihydroxyalkyl furandicarboxylate and dihydroxyalkyl dimer acid obtained in step (1), reacting at a reaction temperature of 150 to 220° C. for 1 to 5 hours to obtain an oligomer, and then completing the reaction while maintaining the reaction temperature to proceed to step (3).
4. The preparation method according to claim 1, characterized in that: The step (3) comprises: adding catalyst B to the oligomer obtained in step (2), controlling the pressure at 40±5 Pa within half an hour, carrying out vacuum polycondensation reaction at a reaction temperature of 220° C., and reacting for 2 to 8 hours; the amount of catalyst B used accounts for 0.3‰ to 0.5‰ of the total mass of the reactants.
Citation Information
Patent Citations
Multi-block copolymer based on 2,5-furandicarboxylic acid polyester and aliphatic polycarbonate, and preparation method of multi-block copolymer
CN110407991A
Coating compositions including a furan-containing polyester, articles, and methods of coating
US20200263053A1
Polycondensate-based pressure-sensitive adhesive containing furan moieties
WO2013034305A1